Green national accounting and sustainability - Löfgren, Karl-Gustaf 1943- (Edward Elgar Pub. Ltd, 2011)
Concerns about natural resource scarcity, together with the increased awareness of environmental problems, has led to widespread interest in green accounting, which attempts to extend the standard national accounts to include the yields from natural and environmental resources. For this volume, Professors Löfgren and Li have selected the classic articles in this rapidly growing area, with particular reference to sustainability. They have also written an authoritative new introduction which offers a comprehensive overview of the literature both from a historical and a formal theoretical perspective. This volume will be an invaluable reference source for scholars and practitioners seeking an in-depth understanding of the main issues in this important field
Keywords: Environmental economics; Environmental auditing; National income / Accounting; Sustainability; Electronic books